Internal mammary node involvement in patients with axilla‐negative early breast cancer: a narrative review. Issue 1 (23rd August 2022) - Braue, Kaela; Baker, Caroline; Lippey, Jocelyn
Abstract: Early breast cancer staging involves radiological and pathological evaluation of the tumour and regional lymph nodes. The internal mammary nodes (IMN) are an important site of possible metastasis and influence disease stage and prognosis. However, the recommendation for routine IMN assessment remains unclear. Internal mammary sentinel lymph node biopsy (SLNB) is associated with increased morbidity and an unknown survival benefit. Furthermore, the IMN are traditionally thought to be involved only synchronous with, or following, axillary node (AXN) metastasis. The aim of this review is to determine the prevalence of IMN metastasis in patients with axilla‐negative early breast cancer. A narrative review of studies assessing IMN metastasis was performed. The literature search was completed using the database Medline (Ovid). Twenty‐two retrospective studies were identified. The studies included data from SLNB, US, MRI, PET/CT and opportunistic biopsy during free‐flap reconstruction (FFR). The prevalence of isolated IMN metastasis ranged from 1.2% to 17.9%. Abstract : The internal mammary nodes are an important site of possible metastasis, however, they are not routinely assessed. This review aims to determine the prevalence of internal mammary node metastasis in patients with axilla‐negative early breast cancer.